Heating and acceleration of ions with Kappa distribution functions by low‐frequency Alfvén wave. Issue 3 (12th October 2021) - Li, Kehua; Li, Jingchun; Lu, Xingqiang; Chen, Shijia
Abstract: Heating and acceleration of ions with Kappa distribution functions (with parameter κ ) in low‐beta plasmas, by a low‐frequency Alfvén wave, is investigated using test‐particle simulations, yielding interesting new results. As long as the Alfvén wave amplitude is sufficiently large, the computed net heating energy of ions becomes independent of the wave frequency and amplitude, always approaching the same value of mv A 2 / 2 . The eventual energy of ions is dictated only by the initial ion energy and the ratio of the magnetic field energy density to the plasma density. The heating effect of the Kappa ions increases with κ . During the heating process, the ions are picked up by the Alfvén wave and pitch angle scattered, forming a quasi‐isotropic spherical shell velocity distribution. The Kappa ions are accelerated in the parallel direction, reaching a bulk flow speed roughly equal to the local Alfvén speed. Higher κ ‐value in the initial Kappa distribution leads to faster saturation. The above results may explain certain features of the ion heating and acceleration in the solar wind and corona.